STRES KERJA DAN MOTIVASI KERJA PENGARUHNYA TERHADAP KINERJA KARYAWAN BANK SYARIAH MANDIRI DI KOTA MAKASSAR - Sahabuddin, Romansyah; Alim Rahmat, Muhammad Rijal; Ayu Sandira, Nur Fadilah (Transpublika Publisher, 2024)
This study aims to determine the effect of work stress, work motivation, and the effect of both simultaneously on the performance of Bank Syariah Mandiri employees in Makassar City. This research was conducted at the Bank Syariah Mandiri Office in Makassar City with a research unit of permanent employees aged 20-40 years with a minimum work period of 1 year and a high school educational background and a maximum of Master degree (S2). The total population is 409 employees spread across 8 branch offices and sub-branches. The method chosen to determine the sample is purposive sampling and proportional sampling method and the results obtained are 202 samples. Furthermore, data collection was carried out using questionnaire, observation, and interview methods. The research hypothesis was tested through multiple regression analysis using the SPSS program. The research shows that work stress and work motivation have a significant influence on the performance of Bank Syariah Mandiri employees in Makassar City. Unmanaged work stress can reduce productivity, loyalty, and increase employee turnover, while good work motivation tends to improve performance.